A History of the Global Influence of Mao Zedong's Works - He, Mingxing. author. aut Link
XVIII, 787 p. 2 illus., 1 illus. in color.
Keywords: An excellent work that presents the research history of Mao Zedong! It is the first book to delve into the history of translating, publishing, and disseminating Mao Zedong's works in over 20 languages. Notably, the translation projects were not only led by the Chinese government but also undertaken by universities and think tanks in the United States, the United Kingdom, Germany, and other Western countries against the backdrop of the Cold War. These projects stemmed from Mao's ideology, personal charisma, and the Western bloc's need to study China. Through an objective evaluation of extensive Chinese archives, the author showcases and discussed the influence of Mao Zedong's thoughts on the world.Mingxing is Professor from school of International Journalism and Communication in Beijing Foreign Studies University(BFSU). Mingxing He is Professor from school of International Journalism and Communication in Beijing Foreign Studies University(BFSU).